The Organotypic Longitudinal Spinal Cord Slice Culture for Stem Cell Study - Joanna Sypecka; Sylwia Koniusz; Maria Kawalec; Anna Sarnowska (Stem Cells International)
The objective of this paper is to describe in detail the method of organotypic longitudinal spinal cord slice culture and the scientific basis for its potential utility. The technique is based on the interface method, which was described previously and thereafter was modified in our laboratory. The most important advantage of the presented model is the preservation of the intrinsic spinal cord fiber tract and the ventrodorsal polarity of the spinal cord. All the processes occurring during axonal growth, regeneration, synapse formation, and myelination could be visualized while being cultured in vitro for up to 4-5 weeks after the slices had been isolated. Both pups and adult animals can undergo the same, equally efficient procedures when going by the protocol in question. The urgent need for an appropriate in vitro model for spinal cord regeneration results from a greater number of clinical trials concerning regenerative medicine in the spinal cord injury and from still insufficient knowledge of the molecular mechanisms involved in the neuroreparative processes. The detailed method of organotypic longitudinal spinal cord slice culture is accompanied by examples of its application to studying biological processes to which both the CNS inhabiting and grafted cells are subjected.